2017
DOI: 10.5152/ejbh.2017.3457
|View full text |Cite
|
Sign up to set email alerts
|

Educational Study to Increase Breast Cancer Knowledge Level and Scanning Participation among Women Working at a University

Abstract: Objective: The aim of the study is to increase the participation level of women in screening programs by increasing the level of knowledge about early diagnosis and screening methods for breast cancer (BC). Materials and Methods:This was a pretest-posttest one group design study held in Eskişehir Osmangazi University, Turkey. The sample consisted of 405 women in all departments of the University. Data were collected using socio-demographic forms and questionnaires. Training about BC was provided for participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…This finding corroborates Yilmaz., et al [31] who reported in a Turkish study that the BSE knowledge scores of women increased significantly from the pre-test to the post-test after 4 weeks of follow-up after BSE training involving videos and didactic lectures. In addition, this finding supports Ozerdogan., et al [32] that an increase in BSE knowledge scores between pre-test and post-test after three weeks of BSE training. Furthermore, this finding is in line with Abasi., et al [33] that reported that BSE knowledge scores increased between pre-test and post-test after 6 months of follow-up after BSE training.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates Yilmaz., et al [31] who reported in a Turkish study that the BSE knowledge scores of women increased significantly from the pre-test to the post-test after 4 weeks of follow-up after BSE training involving videos and didactic lectures. In addition, this finding supports Ozerdogan., et al [32] that an increase in BSE knowledge scores between pre-test and post-test after three weeks of BSE training. Furthermore, this finding is in line with Abasi., et al [33] that reported that BSE knowledge scores increased between pre-test and post-test after 6 months of follow-up after BSE training.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 1.7 million new cases were diagnosed in 2012, representing 11.9% of all cancers diagnosed worldwide in both genders, and 25% of those diagnosed in women [1]. Analyses using Globocan 2012 data have reported that one out of every 25 women in Turkey will develop breast cancer in some period of their lives [2].…”
Section: Introductionmentioning
confidence: 99%